Why and how do middle managers use autonomy in strategy? - Christie, Annabel Hana (Cranfield University, 2020)
This thesis focuses on the research question why and how do middle managers (MMs) use autonomy in strategy. Building on the literature about MM autonomy and flexibility in strategy, I focus on the concept of autonomy in strategy for MMs, which includes when MMs act independently to change or subvert intended strategy, in contrast to MM flexibility in strategy which often supports intended strategy. In an inductive study based on interviews with MMs in large multinational companies from varying countries and industries, I develop four main findings. First, in terms of from where MM autonomy in strategy comes, it has at least three sources: inherent autonomy, situational autonomy, and gained autonomy. Second, in terms of what are the strategy implementation outcomes of MMs’ use of autonomy in strategy, there are four major outcomes: the strategy being avoided, delayed, changed or delivered. Third, looking at why MMs use autonomy in strategy to change strategy, MMs have different motivations: self-interest, they are unclear on the strategy, do not believe in the strategy, or do not implement strategy in response to non-attention by TMs. Fourth, looking at how MMs use autonomy in strategy, MMs have several ways of adapting strategies that they find difficult or do not wish to implement: MMs use prioritisation, capabilities, resources, status, trust, persuasion, networks and politics. I make a theoretical contribution by formulating six propositions about strategy-specific conditions, the sources of MM autonomy in strategy, the self-interest of MMs, and the outcomes of MM autonomy in strategy. These propositions advance our understanding of various aspects of MM autonomy in strategy.
Keywords: flexibility; independent actions; intended stategy; inherent; situational; gained